PENGARUH LATIHAN TEKNIK DASAR SEPAK BOLA TERHADAP KETERAMPILAN PASSING SISWA - Sularno Sularno; Abdur Rahim; Dewi Utami (JOEL: Journal of Educational and Language Research, 2022)
Passing is regarded as important skill when people play soccer. However, the footballers find difficulty to master it. This study aims to determine the effect of basic soccer technique training to improve the passing skills of the students in a private school in Indramayu. This quantitative study uses quasi-experimental design. To collect data, the researcher conducted an observation and gave two tests of pre-test and post-test for two different groups of treatment and control group. A documentation was also taken for data collection. The study found that basic soccer technique training has a significant and positive effect in improving the passing skills of the students.